Solid-State Synthesis, Characterization, and Biological Activity of the Bioinorganic Complex of Aspartic Acid and Arsenic Triiodide - Guo-Qing Zhong; Wen-Wei Zhong; Rong-Rong Jia; Yu-Qing Jia (Journal of Chemistry)
The bioinorganic complex of aspartic acid and arsenic triiodide was synthesized by a solid-state reaction at room temperature. The formula of the complex is AsI3[HOOCCH2CH(NH2)COOH]2.5. The crystal structure of the complex belongs to monoclinic system with lattice parameters: a=1.0019 nm, b=1.5118 nm, c=2.1971 nm, and β=100.28°. The infrared spectra can demonstrate the complex formation between the arsenic ion and aspartic acid, and the complex may be a dimer with bridge structure. The result of primary biological test indicates that the complex possesses better biological activity for the HL-60 cells of the leukemia than arsenic triiodide.